Polarization-independent tunable terahertz slow light with electromagnetically induced transparency metasurface. (1st September 2022) - Devi, Koijam Monika; Jana, Arun; Punjal, Ajinkya; Acharyya, Nityananda; Prabhu, Shriganesh S; Roy Chowdhury, Dibakar
Abstract: Tunable slow light systems have gained much interests recently due to their efficient control of strong light–matter interactions as well as their huge potential for realizing tunable device applications. Here, a dynamically tunable polarization independent slow light system is experimentally demonstrated via electromagnetically induced transparency (EIT) in a terahertz (THz) metasurface constituted by plus and dimer-shaped resonators. Optical pump-power dependent THz transmissions through the metasurface samples are studied using the optical pump THz probe technique. Under various photoexcitations, the EIT spectra undergo significant modulations in terms of its resonance line shapes (amplitude and intensity contrast) leading to dynamic tailoring of the slow light characteristics. Group delay and delay bandwidth product values are modulated from 0.915 ps to 0.42 ps and 0.059 to 0.025 as the pump fluence increases from 0 to 62.5 nJ cm −2 . This results in tunable slow THz light with group velocities ranging from 2.18 × 10 5  m s −1 to 4.76 × 10 5  m s −1, almost 54% change in group velocity. The observed tuning is attributed to the photo-induced modifications of the optoelectronic properties of the substrate layer. The demonstrated slow light scheme can provide opportunities for realizing dynamically tunable slow light devices, delay lines, and other ultrafast devices for THz domain.